2021
DOI: 10.3389/fcell.2021.667551
|View full text |Cite
|
Sign up to set email alerts
|

CIRBP Knockdown Attenuates Tumourigenesis and Improves the Chemosensitivity of Pancreatic Cancer via the Downregulation of DYRK1B

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies worldwide with very limited treatment options. Cold-inducible RNA binding protein (CIRBP) plays promoting roles in several types of cancers, but its function remains unclear in PDAC. Here, we found that the expression of CIRBP was upregulated in PDAC tumor tissues and was significantly associated with poor prognosis. Knockdown of CIRBP in PANC-1 and SW1990 cells inhibited proliferation, migration and invasion in vitro and suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Accumulated evidence reveals that Cirbp has been implicated in different physiological and pathological processes, including cell proliferation and differentiation, cell senescence, cell survival and apoptosis, oxidative stress, DNA damage and repair, immune and inflammatory responses, telomere maintenance, circadian rhythm, spermatogenesis, and tumor formation and progression, etc [ 4 , 10 , 35 , 59 , 61 , 73 , 137 , 138 ]. Furthermore, Cirbp functions as a tumor suppressor in ovarian carcinoma and endometrial carcinoma, whereas Cirbp exerts its pro-tumorigenic roles in pancreatic cancer, breast cancer, colorectal cancer, lung cancer, melanoma, prostate cancer, bladder cancer and skin squamous cell carcinoma [ 10 , 11 , 16 , 41 , 47 , 58 , 59 , 71 , 73 , 137 , 138 ], indicating that Cirbp has context-dependent tumor-suppressive and oncogenic functions in oncogenesis and cancer progression. Our previous study revealed that the significantly decreased expression of Cirbp was found in the clinical specimens of human nasopharyngeal carcinoma (NPC) [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence reveals that Cirbp has been implicated in different physiological and pathological processes, including cell proliferation and differentiation, cell senescence, cell survival and apoptosis, oxidative stress, DNA damage and repair, immune and inflammatory responses, telomere maintenance, circadian rhythm, spermatogenesis, and tumor formation and progression, etc [ 4 , 10 , 35 , 59 , 61 , 73 , 137 , 138 ]. Furthermore, Cirbp functions as a tumor suppressor in ovarian carcinoma and endometrial carcinoma, whereas Cirbp exerts its pro-tumorigenic roles in pancreatic cancer, breast cancer, colorectal cancer, lung cancer, melanoma, prostate cancer, bladder cancer and skin squamous cell carcinoma [ 10 , 11 , 16 , 41 , 47 , 58 , 59 , 71 , 73 , 137 , 138 ], indicating that Cirbp has context-dependent tumor-suppressive and oncogenic functions in oncogenesis and cancer progression. Our previous study revealed that the significantly decreased expression of Cirbp was found in the clinical specimens of human nasopharyngeal carcinoma (NPC) [ 61 ].…”
Section: Introductionmentioning
confidence: 99%